Fiscal Rules in Response to the Crisis : Toward the "Next-Generation" Rules: A New Dataset - Budina, Nina (IMF Working Papers; Working Paper ;, 2012)
Strengthening fiscal frameworks, in particular fiscal rules, has emerged as a key response to the fiscal legacy of the crisis. This paper takes stock of fiscal rules in use around the world, compiles a dataset - covering national and supranational fiscal rules, in 81 countries from 1985 to end-March 2012 - and presents details about the rules' key design elements, particularly in support of enforcement. This information is summarized in a set of fiscal rules indices. Three key findings emerge: (i) many new fiscal rules have been adopted and existing ones strengthened in response to the crisis; (ii) the number of fiscal rules and the comprehensiveness of the design features in emerging economies has caught up to those in advanced economies; and (iii) the "next-generation" fiscal rules are increasingly complex as they combine the objectives of sustainability and with the need for flexibility in response to shocks, thereby creating new challenges for implementation, communication, and monitoring.